Observation of the depassivation effect of attrition on magnesium silicates' direct aqueous carbonation products - Dufourny, Adrien; Julcour, Carine; Esvan, Jérôme; Cassayre, Laurent; Laniesse, Priscillia; Bourgeois, Florent (Frontiers in Climate, 2022)
The main obstacle to the aqueous carbonation of non-serpentinised magnesium silicates is the formation of surface passivation layers, which severely limits the reaction rate rate and thus the overall efficiency of the process.. A technological solution to overcome this problem is to perform the carbonation process inside a stirred bead mill, which aims to the continuously remove the surface by-product layers by attrition. In this work, the aqueous carbonation of ferronickel slag, a mineralogically complex mining waste composed of a Mg/Si rich amorphous phase and a crystalline ferrous forsterite, was studied at 150°C and under 10 bar of CO2 with different operating configurations: carbonation alone (C mode), attrition followed by carbonation (A-C mode) and concomitant attrition and carbonation (AC mode). By careful observation of the mineralogy and the surface of the secondary phases formed using complementary analytical techniques, the article allows a better understanding of the passivation phenomenon inherent to the carbonation of magnesium silicates, and confirms the effectiveness of continuous surface mechanical depassivation for reaching high carbonation rates with this type of material. Comparative analysis of the products obtained with the three operating modes shows that a true synergy takes place between attrition and carbonation due to the combined effect of continuous exfoliation and mechanical activation of particle surface, which goes far beyond the simple increase in surface area due to particle size reduction. While mechanical depassivation is here substantiated by several evidence, the additional mechanochemical activation effect cannot be delineated from experiment; however its beneficial contribution to carbonation is inferred from its observation in A-C mode. The work finds that the synergy between attrition and carbonation also yields very characteristic products. They consist in micrometric agglomerates formed by bound spherical particles a few tens of nanometers in size. These particles themselves contain an entanglement of nanometric grains of carbonates and amorphous silica dispersed inside a magnesium-depleted alumino-siliceous matrix. These results confirm that concomitant attrition and carbonation offers one of the most promising pathways for developing direct aqueous carbonation processes with non-thermally activatable magnesium silicates.